Everyday inclusive Web design: an activity perspective - Shaun K. Kane (Information Research: An International Electronic Journal)
Introduction. The accessibility of Websites to people with disabilities is a problem that affects millions of people. Current accessibility initiatives generally target large government or commercial sites. A rapidly growing segment of online content is created by non-professionals. This content is often inaccessible, thereby excluding users with disabilities. Method. Activity theory is used to provide a model of the activities of non-professional, 'end-user' designers. Drawing from the author's experiences with technology learners, a holistic model of end-user Web design is produced. Analysis. The activity model is divided into three components. The activities of end-user designers, tool designers and Website consumers are examined. Potential barriers to the adoption of accessibility practices are identified. Results. Barriers to accessibility can occur within individual activity systems, or may be caused by interactions between systems. The accessibility of this content cannot be addressed by a single party, but requires collaboration between the designer and toolmaker. End-user designers work within a complex social environment and may face uncertainty regarding their roles as designers that affects their awareness of accessibility. Conclusion. . Increasing the accessibility of user-produced content may require a holistic approach. An activity model may be helpful in producing tools and educational materials